Fetal and childhood development of the intrapulmonary veins in man—branching pattern and structure - Hislop, Alison (1973)
The drainage pattern and the structure of the pulmonary veins have been described quantitatively in a series of fetal and child lungs after injection of the veins with a radio-opaque medium. The drainage pattern of the pre-acinar region is complete by half-way through gestation and corresponds with the growth of the pulmonary arteries. There is new growth of veins within the acinus during childhood. Four types of veins arising from five peripheral sites have been described. The change in dimensions with age have also been measured. A measurable muscle layer could not be found in the walls of the veins before birth though some muscle cells were present from 28 weeks of gestation. The thickness of the muscle coat in any vein was similar at birth and in a 3- and 10-year-old child and in all cases was less than in a pulmonary artery of the same size. The muscle cells were of smaller diameter in the veins than in the arteries. Along any venous pathway between a non-muscular and muscular structure was a region where part of the wall was muscular: these veins were termed partially muscular. Their distribution by size was similar at all ages.